Family values of the youth of the Penza region: marriage and parenthood - A.M. Ivanishko (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2022)
Background. The changes in Russia in the sphere of family and marriage affect key value systems. The transformation of family values affects such functional systems of the family as parenthood, marriage and kinship. The attitude of young people towards marriage and childbearing is an important marker of the manifestation of family values among young people. Materials and methods. To study the value orientations of young people in the field of family relations and the birth of children, the data of the author’s study: “Marriage and cohabitationˮ (2020, n = 520), as well as data from the All-Russian study of reproductive strategies of young people (2019, n = 1600). Results. It was revealed that the values of marriage and parenthood are an important part of the value system of young people, however, there is a massive rejection of early childbearing and marriage without prior cohabitation. Young people associate the postponement of starting a family and having children with objective reasons: financial and housing. Conclusions. The study showed that the following trends are noticeable among the youth of the Penza region: postponing childbirth, normalization of cohabitation, planning for the birth of children, partnership budget in a couple. Attitudes towards family and marriage are mostly positive. The ideas of “childfreeˮ as a conscious choice are practically not common among the youth of the Penza region.